2, 6‐Difluorobenzamide Inhibitors of Bacterial Cell Division Protein FtsZ: Design, Synthesis, and Structure–Activity Relationships. (11th July 2017) - Straniero, Valentina; Zanotto, Carlo; Straniero, Letizia; Casiraghi, Andrea; Duga, Stefano; Radaelli, Antonia; De Giuli Morghen, Carlo; Valoti, Ermanno
Abstract: A wide variety of drug‐resistant microorganisms are continuously emerging, restricting the therapeutic options for common bacterial infections. Antimicrobial agents that were originally potent are now no longer helpful, due to their weak or null activity toward these antibiotic‐resistant bacteria. In addition, none of the recently approved antibiotics affect innovative targets, resulting in a need for novel drugs with innovative antibacterial mechanisms of action. The essential cell division protein filamentous temperature‐sensitive Z (FtsZ) has emerged as a possible target, thanks to its ubiquitous expression and its homology to eukaryotic β‐tubulin. In the latest years, several compounds were shown to interact with this prokaryotic protein and selectively inhibit bacterial cell division. Recently, our research group developed interesting derivatives displaying good antibacterial activities against methicillin‐resistant Staphylococcus aureus, as well as vancomycin‐resistant Enterococcus faecalis and Mycobacterium tuberculosis . The aim of the present study was to summarize the structure–activity relationships of differently substituted heterocycles, linked by a methylenoxy bridge to the 2, 6‐difluorobenzamide, and to validate FtsZ as the real target of this class of antimicrobials. Abstract : Targeting the Z ! The search for innovative targets and potent antibiotics is an important endeavor against a serious health problem. The present study is aimed at broadening structure–activity relationship knowledge for a novel class of antimicrobial agents and demonstrating that these compounds interact with filamentous temperature‐sensitive Z (FtsZ), an essential prokaryotic cell division protein.